Systematic literature review of energy sustainability indicators - Josiane Araújo Martins Brilhante; Meneghetti, Rosiene Rodrigues Pires; Xavier, Thiago Padovani; Marcos Wagner Jesus Servare Junior (Latin American Journal of Energy Research, 2025)
This paper presents a systematic review focused on energy sustainability indicators, applying a methodology based on Knowledge Development Process – Constructivist (ProKnow-C). Recognizing that sustainable development and energy are intrinsically interconnected, since energy drives industrialization, technological progress, and socioeconomic development, while also contributing to environmental challenges, this study highlights the need for indicators to guide the transition toward cleaner energy systems. A literature search was conducted in Scopus and Web of Science, resulting in a total of 7,428 results. Following a filtering process based on the elimination of duplicates, relevance, citation count, and content adherence, a final bibliographic portfolio of 12 papers was compiled. The selected studies evaluate energy systems from technical, economic, and environmental perspectives. The resulting portfolio provides a theoretical foundation for sustainable energy management and offers insights for future research.